2020
DOI: 10.21203/rs.3.rs-100746/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel mechanism of HIV elite control by enriching gut dipeptides as HIV-1 antagonist but Prevotella agonist

Abstract: HIV-1 Elite controllers (EC) are a rare group among HIV-1-infected individuals who can naturally control viral replication for a prolonged period. Due to their heterogeneous nature, no universal mechanism could be attributed to the EC status; instead, several host and viral factors are discussed for playing a role. In this study, we investigated the fecal metabolome and microbiome in a Swedish cohort of EC, treatment-naïve viremic progressors (VP) and HIV-negative individuals (HC). We observed an enrichment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The dipeptide WG-am emerged as notably elevated in elite controllers (ECs) in comparison to viral progressors (VPs) and healthy controls (HCs). We have demonstrated the low toxicity of WG-am both in isolation and in combination with other compounds (Sperk et al, 2021;Cena-Diez et al, 2022). Building on these findings, we have shown that it has anti-HIV-1 activity (Sperk et al, 2021;Cena-Diez et al, 2023a).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The dipeptide WG-am emerged as notably elevated in elite controllers (ECs) in comparison to viral progressors (VPs) and healthy controls (HCs). We have demonstrated the low toxicity of WG-am both in isolation and in combination with other compounds (Sperk et al, 2021;Cena-Diez et al, 2022). Building on these findings, we have shown that it has anti-HIV-1 activity (Sperk et al, 2021;Cena-Diez et al, 2023a).…”
Section: Introductionmentioning
confidence: 62%
“…We have demonstrated the low toxicity of WG-am both in isolation and in combination with other compounds (Sperk et al, 2021;Cena-Diez et al, 2022). Building on these findings, we have shown that it has anti-HIV-1 activity (Sperk et al, 2021;Cena-Diez et al, 2023a). WG-am binds to the CD4 binding pocket of HIV-1 gp120 blocking the interaction between the virus and the CD4 receptor and also inhibits HIV-1 reverse transcription (Cena-Diez et al, 2023a).…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, these dipeptides supported in vitro growth of the bacterial genus Prevotella enriched in EC, pinpointing its influence on the host metabolism. Thus, increased levels of both dipeptides and Prevotella could provide beneficial effects for EC [21]. Given that EC is a rare group of individuals, people living with HIV (PLWH) with longterm treatment were also analyzed.…”
Section: Session 4: "Immune Response In Chronic Viral Infections and ...mentioning
confidence: 99%
“…The dipeptide WG-am emerged as notably elevated in elite controllers (ECs) in comparison to viral progressors (VPs) and healthy controls (HCs). We have demonstrated the low toxicity of WG-am both in isolation and in combination with other compounds (Sperk et al, 2021;Cena-Diez et al, 2022). Building on these findings, we have shown that it has anti-HIV-1 activity (Sperk et al, 2021;Cena-Diez et al, 2023a).…”
Section: Introductionmentioning
confidence: 62%
“…We have demonstrated the low toxicity of WG-am both in isolation and in combination with other compounds (Sperk et al, 2021;Cena-Diez et al, 2022). Building on these findings, we have shown that it has anti-HIV-1 activity (Sperk et al, 2021;Cena-Diez et al, 2023a). WG-am binds to the CD4 binding pocket of HIV-1 gp120 blocking the interaction between the virus and the CD4 receptor and also inhibits HIV-1 reverse transcription (Cena-Diez et al, 2023a).…”
Section: Introductionmentioning
confidence: 84%